INSTRUCTIONAL LEADERSHIP BEHAVIORS OF ISLAMIC SCHOOL PRINCIPALS IN DEVELOPING THE PERFORMANCE OF THE TEACHERS - Muhammad Arifin (International Research-Based Education Journal, 2017)
The current study aimed at describing the instructional leadership behaviors of Islamic school principals in developing the teachers' performance. There were four focuses which were (1) promoting the vision and the mission, (2) reforming the teaching and learning, (3) implementing the teaching and learning practice, (4) creating positive learning climate. This study utilized qualitative approach with multi-site research design. The data was collected by using in-depth interview, observation, and documentation. The data analysis was done by using on-site and cross-site data analysis. To check the credibility of the data, triangulation technique, member check and peer discussion were used. Meanwhile, the audibility check was done by the advisor. The research  showed that the principals: (1) promoted the vision and the mission by (a) communicating with the society and realizing them into the goals of the Islamic schools, (b) implementing them into the programs and the policies that were especially related to the teaching and learning, (2) reformed the teaching and learning by: (a) organizing the teaching and learning through participative and innovative management, (b) having high expectations in teachers' performance and the students' achievement, (3) improved the teaching and learning practice by (a) diagnosing the teaching and learning problems through class supervision and in-service programs depending on the teachers' needs, (b) used the students' learning outcome to improve and to encourage the teachers to utilize the learning sources optimally, (4) creating positive learning climate: (a) created working mechanism which made formal and informal discussion about teaching and learning, (b) created the reward system for the achievements. Keywords:  instructional leadership behaviors, principals of Islamic schools, teachers’ performance